Impact of internal auditing in supporting competitive advantage in Sudanese industrial establishments (Case study- Industrial DAL Company) - Ali, Abu baker Ahmed Yousif Mohammed; Ahmed, Shihabeldeen Mohamed (Journal of Economic, Administrative and Legal Sciences, 2020)
The study tackled the impact of internal auditing in supporting the competitive advantage in Sudanese industrial establishments. A field study on Dal Industrial Company. The research problem was how to activate، the impact of internal auditing in supporting the competitiveness of industrial establishments in Sudan. The research hypotheses were as follows: Initial Hypothesis: There is a statistically significant impact of internal auditing in supporting the competitive advantage. The second hypothesis: Emphasis services in the governance for internal audit in supporting the competitive advantage of industrial facilities. There is a statistically significant effect on the relationship between advisory services as internal auditing in supporting the competitive advantage of industrial establishments. The methodology of the study used descriptive and analysis approach. The researcher used the questionnaire to collect field data. The results were including the recent trends of the impact of internal audit to advise the internal auditor in support the competitive advantage of Company. Recent trends in internal auditing have ensured that information is accurate that helps management make the right decisions and support the competitive advantage. The recommendations، the need for internal audit management to advise and advise the internal auditor. Auditors who have sufficient knowledge of the standards of professional performance. The need to continue to train internal auditors through seminars and attend conferences to keep up with the latest developments of internal audit.
Keywords: internal audit; support competitive advantage; industrial facilities; Sudan